Low-cost alternative renewable energy bioethanol production from palm oil in Malaysian context - Ravindra Pogaku; Tapan Kumar Biswas; Rahmath Abdulla (Springer US, 2013)
Biofuels can be broadly defined as solids, liquids, or gas fuels consisting of, or derived from, plant biomass. Its use here is primarily with respect to a liquid transportation fuel (bioethanol or biodiesel). A major environmental issue being addressed by the global community is the sustainable supply of energy in parallel with a significant reduction in greenhouse gas emissions. This will be a significant technological and socioeconomic challenge because of our dependence on fossil fuel combustion for energy and the fact that it is this combustion that is the primary cause of greenhouse gas emissions.